A construção de um aplicativo no Geogebra como recurso facilitador do ensino-aprendizagem da geometria diferencial de curvas e superfícies - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This work presents the construction of an applet developed in GeoGebra to be used as a facilitator in the teaching-learning process of basic concepts of Differential Geometry of curves and surfaces. We developed the theory of curves and surfaces necessary for the development of the application. We show how we built this application and some difficulties faced, mainly in the interaction of the results of the theory with the resources available in GeoGebra. The Application still needs adjustments and development, mainly, to cover more geometric concepts.
Keywords: GeoGebra; Applet; Interface de programas aplicativos (Software); Matemática - Estudo e ensino; Teoria de curvas e superfícies; CIÊNCIAS EXATAS E DA TERRA; Construção de applet; GeoGebra; Curvas; Superfícies